Stanje in perspektive uporabe govornih virov v raziskavah govora (University of Maribor Press, 2024)
Status and Perspectives of the Use of Speech Resources in Speech Research. The scientific monograph “Status and Perspectives of the Use of Speech Resources in Speech Research” presents the results of the first year of work in the research project Basic Research for the Development of Speech Resources and Technologies for the Slovenian Language (J7-4642), as well as the results of researchers working on speech in other research projects, with the common main goal of the strategic and efficient development of freely accessible speech resources. The contributions highlight plans, objectives, and challenges in building speech resources, especially at the lexical and syntactic levels and seek solutions for the peculiarities of speech at the phonetic-phonological level, also in the context of recording standards of (dialectal) speech. Speech and language variability are explored as manifestations of social complexity, while spoken discourse is also analysed from the perspective of the interaction and interplay of different semiotic codes with regard to their mutual effect in generating the meaning of the message. Selected online texts are analysed from the perspective of the intertwining elements of spoken and written language, not overlooking the role of speech in theatre arts.